"Why We Keep Coming Back": Family and Provider Perspectives on Factors Influencing Long-term Follow-up for Pediatric Cancer Survivorship Care. Issue 1 (16th June 2021) - Gandy, Kellen C.; De Nigris, Francesca B.; Frugé, Ernest; Okcu, Mehmet F.; Schwartz, David D.
Abstract : Purpose: The majority of childhood cancer survivors do not follow-up for long-term risk-based screening for recurrent illness and treatment late effects, despite a high prevalence of secondary morbidities. The primary aim of this study was to investigate factors that influence long-term follow-up for survivorship care, from the perspectives of providers, patients, and caregivers. Materials and Methods: A semistructured interview was designed to elicit stakeholder perspectives on factors that facilitate or impede routine clinic visits after completion of cancer therapy. Results were analyzed using a qualitative framework method. Results: Providers, patients, and caregivers identified a wide range of factors that might influence long-term follow-up for care. All respondents noted the importance of efficient clinical operations, resources such as parking, provider behaviors, rapport/attachment, and patient/family logistics. Compared with patients/caregivers, providers more frequently mentioned institutional operations, their own education and skills, patient/family understanding and motivation, and interpersonal processes such as communication style. Families more frequently mentioned clinic environment, and patients more frequently noted the importance of having a family member present, something neither providers nor caregivers reported. Conclusions: Providers, patients, and patient caregivers have different perspectives regarding factors that may influence follow-up for long-term survivorship care. Understanding these differences can help inform efforts to improve follow-up.